Populasi Lalat Buah (Bactrocera spp.) yang Disampling Menggunakan Metil Eugenol pada Terong (Solanum melongena L.) di Kabupaten Ogan Ilir, Sumatera Selatan - Febrianti, Bella Annisa; Carolin, Jenia; Febriyanti, Nabila; Gresya Ginting, Cesey; Masnita Sinaga, Tessia; Aziz, Muhammad; Umayah, Abu; Gunawan, Bambang; Arsi, Arsi (Seminar Nasional Lahan Suboptimal, 2022)
Febrianti BA, Carolin J, Febriyanti N, Ginting CG, Sinaga TM, Aziz M, Umayah A, Gunawan B, Arsi A. 2022. Population of Fruit Flies (Bactrocera spp.) Sampled Using Methyl Eugenol on Eggplant (Solanum melongena L.) in Ogan Ilir Regency, South Sumatra. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 759-767. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Fruit flies are one of the pests on eggplant plants with a wide distribution, in high populations fruit fly attacks can potentially damage fruit up to 100%. This survey aimed to determine the population of fruit flies on eggplant plants, gender and what species are attracted to methyl eugenol. The method used in carrying out this survey is a sampling method using methyl eugenol modified with a bottle called the hanging bottle trap or attractant trap with a diagonal pattern, which was carried out in 3 replications in Palem Raya Village, Tanjung Pering Village, and Ulak Segelung Village, Indralaya District. North, Ogan Ilir Regency, South Sumatra. The results of the three replicate surveys showed that the population of fruit flies on eggplant plantations in Ulak Segelung Village was higher than in Tanjung Pering Village and Palem Raya Village. The number of fruit fly population sampling in the village of Palem Raya there are 1,426 fruit flies. The fruit fly population in Tanjung Pering Village are 1,276 fruit flies, and in Ulak Segelung Village there are 2,215 fruit flies. Based on the survey conducted, it showed that fruit flies attract to methyl eugenol were male fruit flies with the species Bactrocera dorsalis. There was a decrease in the population in each sampling replication that had been carried out in 3 villages in Ogan Ilir Regency. The conclusion of this survey, that using of methyl eugenol is very effective to determined the population of fruit flies on eggplant plants. The use of methyl eugenol could be used as an alternative material for controlling fruit flies.